Strategies of Motorcycle Enthusiasts in Building a Sakinah Family - Hidayatun Ulfa; Catur Wahyu Kartiko Aji (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
This study examines the strategies employed by motorcycle enthusiasts in maintaining family harmony amid the challenges of modern lifestyles. Motorcycle-related activities such as vehicle modification, touring, and participation in enthusiast communities often require significant time and financial resources, which may potentially generate tension within the household. This research aims to analyze family practices among motorcycle enthusiasts, the strategies they employ to balance hobbies and domestic responsibilities, and the role of wives in supporting and regulating these activities. This study adopts a qualitative research design with a case study approach conducted in Temanggung. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using Miles and Huberman’s interactive data analysis model.The findings indicate that motorcycle-related hobbies do not necessarily have a negative impact on family life. Motorcycle enthusiasts implement various strategies, including open and effective communication with their spouses, careful financial planning, balanced time management, and the internalization of religious values in everyday life. The role of wives is particularly significant in providing emotional support, managing household finances, and reminding their husbands to maintain equilibrium between personal hobbies and family obligations. As a result, families of motorcycle enthusiasts are able to sustain household harmony while pursuing personal interests, thereby embodying the concept of a sakinah family.